The effect of brainstorming, auditor ethics, and whistleblowers on audit opinions of government financial reports: The moderating role of management support - Yasmin, Muhammad; Haliah; Kusumawati, Andi; Darmawati (Asian Economic and Financial Review, 2024)
This research aims to explore the impact of brainstorming (BR), auditor ethics (AE), and whistleblowers (WH) on audit opinions (AO). It also aims to assess the moderating role of management support (MS) in these relationships. The population of this study was 166 auditors from the Supreme Audit Agency (BPK-Badan Pemeriksa Keuangan) spread across the Papua region of Indonesia. The data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis. The findings show that there is a significant influence of brainstorming and auditor ethics on audit opinion, but whistleblowers do not influence audit opinion. In addition, management support moderates the influence of auditor ethics but not brainstorming and whistleblowers. Management that supports auditor ethics strengthens the positive effect of auditor ethics on audit opinions, ensuring that auditors can operate independently and objectively. However, the findings demonstrate that management support is unable to control the impact of brainstorming and whistleblowing on audit opinion, which is a result of other factors that are more important in influencing audit results. This research suggests that effective organizational management is crucial for maintaining auditor ethics and enhancing auditor independence in delivering unbiased audit opinions. Therefore, organizations must pay more attention to the role and support of management in creating a culture that supports integrity and ethics in the audit process.